PENERAPAN STANDAR OPERASIONAL PROSEDUR PT. PELNI SELAKU OPERATOR KAPAL PENUMPANG DI PELABUHAN TELUK BAYUR - Ristu Ardiansyah dan Boiziardi AS (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
PT. Pelni as operator of passenger ships at Teluk Bayur Port has not been able to run properly, various forms of irregularities can still be found. Standard Operating Procedure of PT. Pelni as Passenger Ship Operator at Teluk Bayur Port is still a clearly stated guide of what is expected and implied from all employees in carrying out their daily activities. The application of standard operating procedures has a very important role in the success of government programs. Especially in terms of services to service users, these service users consist of transportation of people and goods. The constraints faced in implementing the Standard Operating Procedure of PT. Pelni as Passenger Ship Operators at Teluk Bayur Port is still weak supervision of implementers of Standard Operating Procedures, socialization of rights and responsibilities to service users who are still lacking and facilities and infrastructure that are less supportive. The solution to overcome these obstacles is the supervision of the executors of the task, the socialization of rights and responsibilities to service users and the fulfillment of facilities and infrastructure so that the SOP can run smoothly.